Linguistic and Psychometric Validation of the Thai Version of Simplified Diabetes Knowledge Scale: A Measure of Knowledge of Diabetes in a Thai Population - Saneh Khunkaew RN, MSc; Ritin Fernandez RN, MSN, PhD; Jenny Sim RN, BAppSc (Nursing) (SAGE Publishing, 2018)
Purpose To develop a linguistically and psychometrically validated Thai version of the Simplified Diabetes Knowledge Scale (T-SDKS) for adults with Type 2 diabetes mellitus (T2DM). Design A cross-sectional study was carried out among people with T2DM. Methods Consecutive sampling was undertaken to recruit participants at the outpatient diabetes clinic of a hospital in Northern Thailand. Results A total of 502 patients with T2DM were recruited. The mean age of the participants was 60.2 years, and 60.5% were female. The T-SDKS attained a reliability coefficient of .79. The item-total correlation value was greater than 0.20 for each item, and the inter-item correlation ranged between 0.03 and 0.49. Respondents attained a mean percentage knowledge score of 42.39% ± 15.45 on T-SDKS. Discussion/conclusions The T-SDKS has demonstrated to be a brief and simple diabetes knowledge assessment tool to use in a busy clinical setting. Implication for practice The findings can be used to improve health education interventions.